Hematologic Paraneoplastic Syndrome in Newly Diagnosed Patients with Lung Cancer - Andika Chandra Putra; Steven Jonathan; Wira Winardi; Elisna Syahruddin (Faculty of Medicine Universitas Airlangga, 2023)
Introduction: Lung cancer could have signs and symptoms generated by paraneoplastic syndromes. This study aimed to describe and analyze hematologic paraneoplastic syndrome in patients with lung cancer in Indonesia. Methods: This was a cross-sectional analytic study conducted in Persahabatan National Respiratory Referral Hospital, Jakarta, between September 2018 and February 2019, on all newly diagnosed patients with lung cancer whose diagnosis was established and who fulfilled the inclusion and exclusion criteria. Results: The mean age of subjects was 56.7 ± 11.4 years old. Most subjects were male, had normal nutritional status (42.6%), had a smoking history (75%), and had a moderate Brinkman Index (BI) value (52%). The most common type of histology was squamous cell carcinoma (SCC) (39.7%), with advanced stage (83.8%) and performance status <2 (94.1%). Paraneoplastic anemia was 40.4%, associated with poor nutritional status and commonly normocytic normochromic anemia. The proportion of paraneoplastic leukocytosis was 39%, associated with males and smoking history. The proportion of paraneoplastic neutrophilia was 51.5%, and it was related to males, smoking history, and SCC histology type. Paraneoplastic hypereosinophilia and thrombocytosis proportions were 2.9% and 18.4%, respectively. The proportion of paraneoplastic hypercoagulability was 91.2%, which was caused by the elevated D-dimer level. Conclusion: The most common hematologic paraneoplastic syndromes in patients with lung cancer were hypercoagulability, neutrophilia, and anemia. The low hemoglobin (Hb) level of paraneoplastic anemia was associated with low body mass index (BMI). Male and smoking history in lung cancer patients were associated with paraneoplastic leukocytosis and/or neutrophilia.